Giant Coronary Aneurysm with Coronary-Pulmonary Artery Fistula in a Jehovah's Witness - Hirofuji, Aina; Furugen, Azusa; Kamada, Takeshi; Yamazaki, Kenji; Kamiya, Hiroyuki; Doi, Hirosato (The Thoracic and Cardiovascular Surgeon Reports, 2023)
With an incidence of 3 in 100 million, giant coronary artery aneurysm (CAA) with coronary artery fistula (CAF) is a very rare condition. To prevent rupture, giant CAA with CAF should be swiftly treated. We present a Jehovah's Witness patient with giant CAA and coronary-pulmonary artery fistula. We resected the giant CAA in one piece, while ligating the CAF, without allogeneic blood transfusion. Due to rarity of these conditions, many thoracic surgeons lack direct experience in its surgical procedures. Herein, we share footage of this surgery as an example of how to safely resect CAA with minimal bleeding.
Keywords: giant coronary artery aneurysm; coronary-pulmonary artery fistula; Jehovah's Witness